PENERAPAN ALAT PERAGA SERI-PARALEL DC UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI HUKUM OHM - Galuh Ayu Riyanti; Sutikno Sutikno; Masturi Masturi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The aim of this study is to find out the use of series-paralel DC demonstrating tools to improve students’ understanding in Ohm law. This study uses Pre-Experimentalwith One-Group Pretest-Posttest design. The population used was all XI grade students of a vocational school in Pemalang regency in the academic year of 2014-2015. The sample of the study were students of class XI TP 1 who were taken accordingly by purposive sampling. The tecniques used were observation, test, and interview. The result shows that the use of series-paralel DC demonstrating tools can improve students’ understanding in Ohm law. Keywords : Demonstrating tools; Ohm law; Understanding.